Letter : Situation in Asturias - Edwards, Ebby
011-0031-001 Telephone. MUSEUM 8886 TELEGRAMS MINFEDBRIT. WESTCENT. LONDON THE MINEWORKERS' FEDERATION OF GREAT BRITAIN 50 Russell Square, London W.C.1 22nd October 1937. SECRETARY Ebby Edwards Sir Walter Citrine, K.B.E., The Trades Union Congress General Council, Transport House, Smith Square, London, S.W.1. Dear Sir Walter, Situation in Asturias. Thanks for your letter of the 21st inst. to hand this morning in which you enclose copy of a letter you have received from Mr. O. Harris regarding the above subject. As nearly all my Executive Committee have volunteered to go to Gijon if necessary, I am also having letters as if all one had to do in such a case was to get tickets for a W.T.A. cruise. Yours sincerely Ebby Edwards Secretary 292/946/11/31